Development of CO₂-ceramsite foam concrete: Mechanical properties, microstructure and environmental benefits - Jing Zhang; Yuxin Su; Hongshuai Gao (Case Studies in Construction Materials, 2025)
With the advancement of the global carbon neutrality goal, the construction industry, as a major resource consumption and carbon emission sector, is facing increasingly severe environmental pressures. Building material production not only consumes substantial energy but also generates significant CO₂ emissions. This context necessitates the development of novel low-carbon materials and carbon sequestration technologies. This study proposes a novel CO₂-foamed ceramsite foam concrete (CCFC), and systematically investigates its mechanical properties, multi-scale pore structure evolution, and environmental benefits through experimental approaches. CO₂ foaming significantly refined the pore structure of CCFC, enhancing its compressive strength and water absorption capacity while reducing thermal conductivity. Multi-scale analyses from macro to micro levels revealed that CaCO₃ generated through carbonation filled pores and optimized pore distribution. Life cycle assessment (LCA) demonstrated that each cubic meter of CCFC sequesters approximately 25 kg CO₂, reducing global warming potential (GWP) by 12 % compared to conventional ceramsite foam concrete (CFC). These findings indicate that CCFC can serve as a sustainable alternative to traditional insulation materials in building envelopes, significantly lowering carbon footprints in construction projects. By integrating CO₂ sequestration into lightweight concrete production, this technology aligns with global carbon neutrality goals and offers a scalable solution for reducing embodied carbon in urban infrastructure. Furthermore, the improved mechanical and thermal performance of CCFC supports its application in energy-efficient buildings, contributing to both structural safety and long-term energy savings. The findings offer practical guidance for scaling low-carbon construction practices. Compared to other emerging low-carbon concretes such as geopolymer or mineralized systems, CCFC demonstrates a balanced integration of environmental performance, structural applicability, and industrial scalability.